ROLE AND IMPORTANCE OF OUTDOOR GAMES IN INCREASING PHYSICAL ACTIVITY OF CHILDREN (TAMADDUN NURI JURNALI, 2024)
This article focuses on the fact that the inclusion of active games in the educational process of young children helps to solve a number of special problems with high efficiency, as well as increase their interest in sports activities. The use of active games as a method and exercise in the learning process from an early age gives high results, and also plays an important role in increasing their motor activity.